HUMAN CAPITAL ACCUMULATION AND SUB-REPLACEMENT FERTILITY IN AN EU-ADJACENT ECONOMY - DEĞİRMENCİ, Serkan and Özgül ÖZKAN-DEĞİRMENCİ, Hayriye (Journal of European Economy, 2026)
This article examines sub-replacement fertility in Türkiye as an economic outcome of large-scale human capital accumulation under institutional constraints. Over the past two decades, Türkiye has experienced rapid growth in tertiary education participation, particularly among women, while simultaneously converging toward persistent sub-replacement fertility levels comparable to those observed in several European economies. Rather than treating education as an individual-level characteristic, the study conceptualizes human capital accumulation as a structural transformation that reshapes labor market incentives, household decision-making, and reproductive outcomes. Using a descriptive–analytical approach based on official statistical data, the article documents the changes in fertility levels, timing of childbearing, parity distribution, educational differentials, household structure, and regional variation. The results demonstrate that subreplacement fertility in Türkiye is structural rather than cyclical and is most pronounced among women with higher levels of education. The original scientific contribution of the study lies in demonstrating that sub-replacement fertility consti tutes an unintended demographic externality of human capital accumulation in an EU-adjacent economy where institutional arrangements insufficiently support the reconciliation of education, employment, and parenthood. The findings highlight the structural limitations of conventional pro-natalist policies and underscore the necessity of aligning education, labor market, and family policy frameworks. JEL: I23, J13, J18, J24.